Temperature Dependent Electrical and Electrocaloric Properties of Textured 0.72PMN - 0.28PT Ceramics* - Bobrek, Irem; Berksoy-Yavuz, Ayse; Kaya, M. Yunus; Alkoy, Sedat; Okatan, M. Baris (Taylor and Francis Ltd., 2021)
Lead magnesium niobate (PMN) - lead titanate (PT) solid solution ceramics in the ratio of 0.72PMN-0.28PT was produced by a combination of tape-casting in ⟨001⟩pc textured and random forms. The Lotgering factor, f, of textured ceramics was approximately calculated as 80%. Modified Curie-Weiss analysis indicated relaxor dominant behavior for both the random and textured ceramics. Development of texture led to an enhancement in the electromechanical properties with converse piezoelectric charge coefficient (d33*) under 20 kV/cm electric field reaching 545 pm/V for the textured ceramic. Electrocaloric (EC) behavior of random and textured ceramics were obtained from indirect measurements using temperature dependent polarization vs. electric field hysteresis loops. An EC temperature change (ΔTEC) of ∼0.5 K was calculated from the PMN-28PT ceramics at around 80 °C under an electric field of 60 kV/cm. Development of texture was demonstrated to have led to an anisotropy in the EC response.
Keywords: electrical properties; electrocaloric; PMN-PT; texture